Ensino de rítmica musical: analisando uma prática pedagógica bem sucedida. - Cavalcante, Fred Siqueira (Universidade Federal de São Carlos, 2004)
From different regards, the present study has the foremost aim of understanding the trajectory and pedagogical practice of a musical rhythm teacher, José Eduardo Gramani, so that the knowledge produced during the course of the research might serve as a fundamental element for the formation of new musical educators. Understanding his professional trajectory, his specific formation, his beliefs, values and opinions (about school, student, work methodology, the musical "teaching/learning" process), it was sought to set, within and through the related complex of factors and in their intrinsical relationships, what researchers in the field of education have called "teacher s thought" (an interpretation for the course of acquaintance with specific contents towards the pedagogic knowledge as on "a double side-way"), that, in the specific case of this piece of work, it refers to that musical educator. The data have been collected by means of semi-structured interviews, with open schedule. Such interview route, or schedule, was structured through basis upon authors who have studied histories of teachers life, and others who have studied professional trajectories of "good" teachers. Among the interviewees, some were relatives of the above-mentioned teacher, students, co-workers teachers. As collaborators in a collective game, those participants represent all those who, at any rate, have collaborated, so as to Gramani be able to idealize and create his teaching methodology. Paralleled with the above-mentioned procedures, it was made a documental analysis of books that mention facts of this musician s personal history, as well as the available didactic materials produced during his professional teaching trajectory (from the apostils of the beginning of his career till the books later published), specially the reflecting texts on the specific area of musical rhythm teaching, that fit in those materials. The data collected in the interviews and in the documents were analyzed, so as to stand out this teacher s trajectory of personal life and pedagogic actuation, as well as to configure his profile, from the perspective of the interviewees, participants of this research. The analysis main points are sectioned into four themes, all of them obviously referring to the educator aimed at this search; the first theme describes his historical professional and personal trajectory, divided into phases; the second expatiates unpon his beliefs and values related to teaching and human acquaintance; the third analyzes his professorial practice, as well as the development of his knowledge bases that involve such activity ; and the fourth specifies the individual and professional characteristics that compose the teacher s profile, according to the interviewees standpoints. The results give evidence that the educator s performance, accomplished under the criteria based on his beliefs and values, and on his relashionship with the students, have been successful. Other aspects of that practice define peculiar standards of teaching, profitable to composing the cast of knowledges in the studies of those who prepare to exercise the teaching of music, or even of other cognizance áreas.
Keywords: Professores - formação; Educação musical; Músico - educador; Gramani, José Eduardo; Rítmica musical; Music educator; Music rhythm; Music education; CIENCIAS HUMANAS::EDUCACAO